Analisis Pemahaman Mahasiswa Terhadap Pengendalian Sampah Plastik Di Perguruan Tinggi - Gloria Sirait; Irving Josafat Alexander; Melfa Uli Magalena Purba; Kristina Lestari Siahaan; Xenia S. Miranda (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
Plastic waste in university environments has become a crucial issue that affects the cleanliness and sustainability of educational ecosystems. This study aims to analyze the responses of students at HKBP Nommensen University Pematangsiantar regarding plastic waste control on campus. Using a descriptive quantitative approach, data were collected through questionnaires from 30 student respondents and analyzed by percentage. The results show that although students have a high level of understanding of the importance of plastic waste control and its negative impacts, there is still a gap between knowledge and actual behavior in daily campus life. The main obstacles identified include the lack of program socialization and limited student involvement. This study concludes that increasing program effectiveness, providing equitable facilities, and fostering environmentally friendly habits are essential. It is recommended to actively involve students in environmental initiatives and to conduct further research to expand the scope and depth of understanding of student environmental behavior.